Doing Security - Button, M. author. aut Link
XVIII, 264 p.
Keywords: Despite the growing interest in security amongst governments, organizations and the general public, the provision of much security is substandard. This book explores the problems facing security, and sets out innovative proposals to enhance the effectiveness of security in society, at national and organizational levels.